Supplement use in the older population of Iceland. Multivitamin use and risk of cardiovascular disease mortality - Birta Ólafsdóttir 1989- (2016)
Background and aims: Chronic diseases remain the most common cause of death world-wide, the main contributor of which is cardiovascular disease. Supplements are often taken in the belief that they can prevent chronic disease, but another common reason for their use is poor nutritional status. The use of supplements has increased widely in recent years and a large proportion of adults use supplements. Multivitamins are the most commonly used supplement worldwide and the use seems to increase with age. The objective of this thesis is to describe the use of supplements among the elderly and to assess the association of multivitamins with the risk of death due to cardiovascular disease. Methods: Information on the use of supplements was obtained from the Age, Gene/Environment Susceptibility (AGES-Reykjavik) Study, a prospective cohort carried out in 2002-2006 by the Icelandic Heart Association. The cohort was established from the Reykjavik Study which was conducted during 1967-1991. Participants were 66-98 years old at baseline of the AGES-Reykjavik study. Information about names of supplements used were obtained and matched with records from the Icelandic Food and Veterinary Authority (MAST) on ingredients of supplements, for estimations of use of vitamins and minerals from supplements. In the first part of this thesis the use of supplements among participants (n = 5,764) was examined as well as the amount of micronutrients obtained from supplements. The use was examined with respect to health, including the use of medications, clinical blood values and other characteristics. Detailed information about health and characteristics of users and nonusers of supplements has often been lacking in previous studies and the AGES-Reykjavik study is exceptionally comprehensive when it comes to these factors. In the second part of this thesis the association of use of multivitamins and cardiovascular disease mortality was examined. Hazard ratios for cardiovascular mortality were calculated with 95% confidence interval (CI) ...